2016
DOI: 10.2217/fon-2016-0168
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors, Predictive Markers and Cancer Biology: The Triad for Successful Oral Cancer Chemoprevention

Abstract: Oral squamous cell carcinomas represent a significant cancer burden worldwide. Unfortunately, chemoprevention strategies investigated to date have failed to produce an agent considered standard of care to prevent oral cancers. Nonetheless, recent advances in clinical trial design may streamline drug development in this setting. In this manuscript, we review some of these improvements, including risk prediction tools based on molecular markers that help select patients most suitable for chemoprevention. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…A working classification along with some of the markers with prognostic significance is listed in Table 3. [117][118][119][120][121][122][123] It is observed that site-wise distribution of OSCC is responsible for intra and inter-tumoural heterogeneity. In this regard, some authors studied buccal mucosa and tongue OSCC for possible heterogeneity in the cell cycle regulatory mechanism by comparing major cell cycle regulatory proteins.…”
Section: Molecular Markersmentioning
confidence: 99%
“…A working classification along with some of the markers with prognostic significance is listed in Table 3. [117][118][119][120][121][122][123] It is observed that site-wise distribution of OSCC is responsible for intra and inter-tumoural heterogeneity. In this regard, some authors studied buccal mucosa and tongue OSCC for possible heterogeneity in the cell cycle regulatory mechanism by comparing major cell cycle regulatory proteins.…”
Section: Molecular Markersmentioning
confidence: 99%
“…until now, a panel of molecular markers has not been determined that allows for a prognostic prediction of oral squamous cell carcinoma. However, these new markers could be considered complementary to conventional prognostic evaluation (Monteiro de Oliveira Novaes and William, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of precision medicine approaches for the treatment of HNC, MALDI-MSI is capable of supporting the strategy of integrating molecular prognostic and predictive marker and cancer biology. [42] Our study reveals the potential MALDI-MSI holds for clinical applications. In contrast to classical histopathological methods, it makes it possible to detect different markers in one tissue section and with a single measurement.…”
Section: Discussionmentioning
confidence: 79%
“…In the context of precision medicine approaches for the treatment of HNC, MALDI–MSI is capable of supporting the strategy of integrating molecular prognostic and predictive marker and cancer biology …”
Section: Discussionmentioning
confidence: 99%